Inter-cultural Communication of Bapuq Dana Ritual at Multiethnic Communities and Trans- religious - Kartika, Komang Reza (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to conduct a study of intercultural communication in ritual practices of Bapuq Dana that involve an active role of multi-ethnic and trans-religious, namely communities of Sasak- Moslem, Bali-Hindus, and Sasak-Buddhist in Tanjung sub-district, North Lombok Regency. Based on the results of this study found three dizziness findings. First, the historical background of Bapuq Dana ritual is closely related to the results of thoughts, feelings and behavior as a form of tribute to a generous figure, namely RadenWiradana regardless of cultural background, religion, social and a number of other differences. Second, the process of Bapuq Dana rituals by the Sasak-Moslem community is carried out by zikir (prayers according to Islamic religion) around the Bapuq Dana patilasan (a place that has been visited or inhabited by Bapuq Dana), the Bali-Hindu community through the implementation of prayers in Pangsung temple to Ida Sang Hyang WidhiWasa (God Almighty) before carrying out the Bapuq Dana ritual.Third, intercultural communication is actualized through interpersonal communication in a series of Bapuq Dana rituals. Intercultural communication is about to realize social interaction which in its accumulation builds tolerance in the plurality.